The Malay Monarchies in Constitutional and Social Conception. Issue 3 (October 2022) - Harding, Andrew; Kumarasingham, Harshan
Abstract: This article examines the constitutional nature of the Malaysian monarchies in their social context. We discuss the evolution of the monarchies through pre-colonial, colonial, and post-colonial history, and account for their survival despite several attempts to curb their powers, including restriction of the royal assent and sovereign immunity. It is argued that the powers of the monarchies respond to their historical role and social embeddedness of the monarchies, stretching the role of the Rulers beyond the Westminster norms as set out in constitutional texts. Moving to contemporary issues, we see the assertion of the right to uphold the Constitution in relation to prime-ministerial appointments, and acting on advice. Here, the monarchies reflect a braiding of both traditional elements and Westminster constitutional norms.